Underglaze blue glaze, underglaze blue ceramics and preparation method thereof

By using materials such as modified quartz and doped nano-alumina in under-glaze blue ceramics, combined with the sintering process and the coordination of nano-boron oxide, the lubricity, stain resistance and scratch resistance of under-glaze blue ceramics have been solved. It solves the problem of poor stability, significantly improves the stability of the glaze surface to acids, alkalis and solvents, and improves the use efficiency of the product.

CN119038954BActive Publication Date: 2025-01-24FUJIAN DEHUA YIHONG IND & TRADE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411549056.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24
Estimated Expiration
2044-11-01

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramics, and in particular to an underglaze blue glaze, an underglaze blue ceramic and a preparation method thereof, comprising the following steps: firstly coloring a glaze pigment onto a ceramic substrate with a coloring thickness of 0.1 mm, and then applying a glaze substrate with a glaze application amount of 100 g / m 2 , and finally sintering treatment to obtain underglaze blue colored ceramics. The underglaze blue colored ceramics of the present invention are prepared by ball clay, potassium feldspar, bentonite, wollastonite and silicon nitride raw materials in a proportioned combination, ball milling, pressing and molding to obtain a ceramic matrix, and the raw materials are mutually blended and coordinated, and then the underglaze blue colored glaze water is prepared to prepare the ceramic product, which has excellent lubricity, and at the same time, the lubricity, stain resistance and scratch resistance are balanced and improved, and the glaze surface has significant acid and alkali resistance and solvent resistance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic glazes, and in particular to an underglaze blue glaze, an underglaze blue ceramic and a preparation method thereof. Background Art

[0002] Ceramics is a general term for pottery and porcelain. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but have poor plasticity. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology.

[0003] Existing underglaze blue-colored ceramics have poor lubricity, and the product has poor stain resistance and scratch resistance. It is difficult to improve the lubricity, stain resistance and scratch resistance in a balanced manner, which limits the product's efficiency. The glaze also has poor acid, alkali and solvent resistance, which limits the product's efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an underglaze blue glaze, an underglaze blue ceramic and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing underglaze blue colored ceramics, comprising the following steps:

[0007] Step 1: Preparation of ceramic substrate:

[0008] According to weight, 20-25 parts of ball clay, 10-15 parts of potassium feldspar, 5-8 parts of bentonite, 4-7 parts of wollastonite, 2-5 parts of silicon nitride and 8-12 parts of water are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material;

[0009] The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix;

[0010] Step 2: Preparation of underglaze blue glaze:

[0011] First prepare the glaze pigment body, and then prepare the glaze base body;

[0012] The glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water;

[0013] The glaze matrix comprises the following raw materials in parts by weight:

[0014] 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent;

[0015] Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

[0016] Preferably, the specific steps of the sintering process are:

[0017] First, sinter at 1250°C for 1-2h, then heat to 1310-1320°C at a rate of 2-4°C / min, keep warm for 4h, and finally air-cool to room temperature.

[0018] Preferably, the preparation method of the modified quartz body is:

[0019] S01: preheating quartz powder at 60-65°C for 10-15 minutes, then keeping the temperature, and fully mixing 5-8 parts of the kept temperature quartz powder, 3-5 parts of lanthanum chloride solution and 1-3 parts of silane coupling agent KH560 by weight to obtain a quartz modifier;

[0020] S02: calcining kaolin at 120-130°C for 20-30min, then heating to 200-220°C at a rate of 2-5°C / min, keeping the temperature for 10min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent;

[0021] S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide;

[0022] By weight, 2-5 parts of modified nano boron oxide and 1-3 parts of nano silica sol are added to 5-8 parts of 5% chitosan solution, and then 2-3 parts of sodium dodecylbenzene sulfonate are added and mixed thoroughly to obtain a treatment solution;

[0023] S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified quartz body.

[0024] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%; the speed of the stirring treatment in S03 is 550-750r / min, and the stirring time is 20-30min.

[0025] Preferably, the preparation method of the doped nano-alumina agent is:

[0026] S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0027] S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid;

[0028] The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent.

[0029] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0030] Preferably, the preparation method of the synergist is:

[0031] The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whisker; 5-8 parts of dry boron carbide whisker and 2-4 parts of nano-bentonite are added to 5-8 parts of sodium lignin sulfonate solution by weight, and then 1-3 parts of dopamine hydrochloride solution and 1-2 parts of stearic acid are added and mixed and stirred sufficiently, and after stirring, the mixture is washed with water, filtered and dried to obtain a performance adjuster.

[0032] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0033] The present invention also provides an underglaze blue glaze for use in the preparation method of underglaze blue ceramics, comprising a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water;

[0034] The glaze matrix comprises the following raw materials in parts by weight:

[0035] 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent.

[0036] The invention also provides an underglaze blue colored ceramic, which is prepared by the preparation method of the underglaze blue colored ceramic.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The underglaze blue colored ceramics of the present invention are prepared by mixing ball clay, potassium feldspar, bentonite, wollastonite and silicon nitride as raw materials, ball milling and pressing to obtain a ceramic matrix, and the raw materials are mutually blended and coordinated, and then the underglaze blue colored glaze is prepared by glazing. The ceramic product has excellent lubricity, and the lubricity, stain resistance and scratch resistance are balanced and improved, and the acid and alkali resistance and solvent resistance of the glaze surface are remarkable;

[0039] 2. The glaze pigment is prepared by cobalt oxide, methyl cellulose, manganese oxide and water, applied to the ceramic substrate, and then combined with the glaze substrate to make an underglaze blue ceramic product. The glaze substrate is coordinated and matched by modified quartz, dolomite, calcined talc, calcium carbonate and doped nano-alumina agent. The modified quartz and doped nano-alumina agent are coordinated and enhanced to improve the lubricity, stain resistance and scratch resistance of the obtained product, and the acid, alkali and solvent resistance of the glaze surface are significantly improved;

[0040] 3. The modified quartz body is preheated with quartz powder, and then mixed with lanthanum chloride solution and silane coupling agent KH560 to fully blend, and then improved by treatment liquid treatment. The treatment liquid is modified nano boron oxide, nano silica sol, chitosan solution with a mass fraction of 5% and sodium dodecylbenzene sulfonate to fully blend. Through the coordination and coordination between the raw materials, the coordinated effect of modified nano boron oxide and quartz powder is optimized to enhance the lubricity of the system. At the same time, the modified nano boron oxide is calcined at 120-130°C for 20-30min with kaolin, and then heated to 200-220°C at a rate of 2-5°C / min, kept warm for 10min, and finally air-cooled to room temperature. Through step-by-step thermal improvement, the layer structure and activity of kaolin are optimized, and yttrium nitrate solution is used, and then nano boron oxide is coordinated and coordinated. Through the coordination between the raw materials, the modified quartz body obtained optimizes the coordination of system performance in the system and improves the performance stability of the product.

[0041] 4. The doped nano-alumina agent uses nano-alumina that is irradiated with protons to stimulate its active performance, and then coordinated with sodium silicate solution and sodium alginate solution to facilitate better coordination of the performance-adjusting agent into the system. The performance-adjusting agent is stirred with potassium permanganate solution through boron carbide whiskers to optimize the active performance of the whiskers, and then coordinated with nano-bentonite, sodium lignin sulfonate solution, dopamine hydrochloride solution and stearic acid. Through the mutual coordination and assistance between the raw materials, the coordinated effect of the doped nano-alumina agent and the modified quartz body is better, and the performance of the product is further improved. DETAILED DESCRIPTION

[0042] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] A method for preparing underglaze blue colored ceramics of this embodiment comprises the following steps:

[0044] Step 1: Preparation of ceramic substrate:

[0045] According to weight, 20-25 parts of ball clay, 10-15 parts of potassium feldspar, 5-8 parts of bentonite, 4-7 parts of wollastonite, 2-5 parts of silicon nitride and 8-12 parts of water are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material;

[0046] The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix;

[0047] Step 2: Preparation of underglaze blue glaze:

[0048] First prepare the glaze pigment body, and then prepare the glaze base body;

[0049] The glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water;

[0050] The glaze matrix comprises the following raw materials in parts by weight:

[0051] 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent;

[0052] Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

[0053] The specific steps of the sintering process in this embodiment are:

[0054] First, sinter at 1250°C for 1-2h, then heat to 1310-1320°C at a rate of 2-4°C / min, keep warm for 4h, and finally air-cool to room temperature.

[0055] The preparation method of the modified quartz body of this embodiment is:

[0056] S01: preheating quartz powder at 60-65°C for 10-15 minutes, then keeping the temperature, and fully mixing 5-8 parts of the kept temperature quartz powder, 3-5 parts of lanthanum chloride solution and 1-3 parts of silane coupling agent KH560 by weight to obtain a quartz modifier;

[0057] S02: calcining kaolin at 120-130°C for 20-30min, then heating to 200-220°C at a rate of 2-5°C / min, keeping the temperature for 10min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent;

[0058] S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide;

[0059] By weight, 2-5 parts of modified nano boron oxide and 1-3 parts of nano silica sol are added to 5-8 parts of 5% chitosan solution, and then 2-3 parts of sodium dodecylbenzene sulfonate are added and mixed thoroughly to obtain a treatment solution;

[0060] S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified quartz body.

[0061] The mass fraction of the lanthanum chloride solution of the present embodiment is 2-5%; the speed of the stirring treatment in S03 is 550-750r / min, and the stirring time is 20-30min.

[0062] The preparation method of the doped nano-alumina agent of this embodiment is:

[0063] S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0064] S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid;

[0065] The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent.

[0066] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0067] The preparation method of the performance modifier of this embodiment is:

[0068] The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whisker; 5-8 parts of dry boron carbide whisker and 2-4 parts of nano-bentonite are added to 5-8 parts of sodium lignin sulfonate solution by weight, and then 1-3 parts of dopamine hydrochloride solution and 1-2 parts of stearic acid are added and mixed and stirred sufficiently, and after stirring, the mixture is washed with water, filtered and dried to obtain a performance adjuster.

[0069] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0070] The underglaze blue glaze of the present embodiment is used in the above-mentioned method for preparing an underglaze blue ceramic, comprising a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water;

[0071] The glaze matrix comprises the following raw materials in parts by weight:

[0072] 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent.

[0073] The underglaze blue colored ceramic of the present embodiment is prepared by the above-mentioned preparation method of the underglaze blue colored ceramic.

[0074] Embodiment 1: A method for preparing underglaze blue colored ceramics, comprising the following steps:

[0075] Step 1: Preparation of ceramic substrate:

[0076] According to weight, 20 parts of ball clay, 10 parts of potassium feldspar, 5 parts of bentonite, 4 parts of wollastonite, 2 parts of silicon nitride and 8 parts of water were mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material;

[0077] The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix;

[0078] Step 2: Preparation of underglaze blue glaze:

[0079] First prepare the glaze pigment body, and then prepare the glaze base body;

[0080] The glaze pigment body is prepared by weight from 20 parts of cobalt oxide, 3 parts of methyl cellulose, 2 parts of manganese oxide and 10 parts of water;

[0081] The glaze matrix comprises the following raw materials in parts by weight:

[0082] 10 parts of modified quartz, 8 parts of dolomite, 6 parts of calcined talc, 4 parts of calcium carbonate, and 3 parts of doped nano-alumina agent;

[0083] Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

[0084] The specific steps of the sintering process in this embodiment are:

[0085] First, sinter at 1250°C for 1 h, then heat to 1310°C at a rate of 2°C / min, keep at that temperature for 4 h, and finally air-cool to room temperature.

[0086] The preparation method of the modified quartz body of this embodiment is:

[0087] S01: preheating quartz powder at 60° C. for 10 min, then keeping the temperature, and fully mixing 5 parts of the kept temperature quartz powder, 3 parts of lanthanum chloride solution, and 1 part of silane coupling agent KH560 by weight to obtain a quartz modifier;

[0088] S02: calcining kaolin at 120°C for 20 min, then heating to 200°C at a rate of 2°C / min, keeping the temperature for 10 min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent;

[0089] S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide;

[0090] According to weight, 2 parts of modified nano boron oxide and 1 part of nano silica sol are added to 5 parts of 5% chitosan solution, and then 2 parts of sodium dodecylbenzene sulfonate are added and mixed thoroughly to obtain a treatment solution;

[0091] S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified quartz body.

[0092] The mass fraction of the lanthanum chloride solution in this embodiment is 2%; the speed of the stirring process in S03 is 550r / min, and the stirring time is 20min.

[0093] The preparation method of the doped nano-alumina agent of this embodiment is:

[0094] S11: irradiating the nano-alumina in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0095] S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid;

[0096] The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent.

[0097] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 3%.

[0098] The preparation method of the performance modifier of this embodiment is:

[0099] The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whiskers; 5 parts of dry boron carbide whiskers and 2 parts of nano-bentonite are added to 5 parts of sodium lignin sulfonate solution by weight, and then 1 part of dopamine hydrochloride solution and 1 part of stearic acid are added and mixed and stirred sufficiently. After stirring, the mixture is washed with water, filtered and dried to obtain an efficiency regulator.

[0100] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 3%.

[0101] The underglaze blue glaze of this embodiment is used in the above-mentioned method for preparing an underglaze blue ceramic, comprising a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 20 parts of cobalt oxide, 3 parts of methyl cellulose, 2 parts of manganese oxide and 10 parts of water;

[0102] The glaze matrix comprises the following raw materials in parts by weight:

[0103] 10 parts of modified quartz, 8 parts of dolomite, 6 parts of calcined talc, 4 parts of calcium carbonate, and 3 parts of doped nano-alumina agent.

[0104] The underglaze blue colored ceramic of the present embodiment is prepared by the above-mentioned preparation method of the underglaze blue colored ceramic.

[0105] Embodiment 2: A method for preparing underglaze blue colored ceramics, comprising the following steps:

[0106] Step 1: Preparation of ceramic substrate:

[0107] According to weight, 25 parts of ball clay, 15 parts of potassium feldspar, 8 parts of bentonite, 7 parts of wollastonite, 5 parts of silicon nitride and 12 parts of water were mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material;

[0108] The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix;

[0109] Step 2: Preparation of underglaze blue glaze:

[0110] First prepare the glaze pigment body, and then prepare the glaze base body;

[0111] The glaze pigment body is prepared by weight from 25 parts of cobalt oxide, 6 parts of methyl cellulose, 3 parts of manganese oxide and 20 parts of water;

[0112] The glaze matrix comprises the following raw materials in parts by weight:

[0113] 15 parts of modified quartz, 12 parts of dolomite, 10 parts of calcined talc, 7 parts of calcium carbonate, and 5 parts of doped nano-alumina agent;

[0114] Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

[0115] The specific steps of the sintering process in this embodiment are:

[0116] First, sinter at 1250°C for 2h, then heat to 1320°C at a rate of 4°C / min, keep at that temperature for 4h, and finally air-cool to room temperature.

[0117] The preparation method of the modified quartz body of this embodiment is:

[0118] S01: preheating quartz powder at 65° C. for 15 min, then keeping the temperature, and fully mixing 8 parts of the kept temperature quartz powder, 5 parts of lanthanum chloride solution and 3 parts of silane coupling agent KH560 by weight to obtain a quartz modifier;

[0119] S02: calcining kaolin at 130°C for 30 min, then heating to 220°C at a rate of 5°C / min, keeping the temperature for 10 min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent;

[0120] S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide;

[0121] By weight, 5 parts of modified nano boron oxide and 3 parts of nano silica sol were added to 8 parts of 5% chitosan solution, and then 3 parts of sodium dodecylbenzene sulfonate were added and mixed thoroughly to obtain a treatment solution;

[0122] S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified quartz body.

[0123] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the speed of the stirring process in S03 is 750r / min, and the stirring time is 30min.

[0124] The preparation method of the doped nano-alumina agent of this embodiment is:

[0125] S11: irradiating the nano-alumina in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0126] S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid;

[0127] The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent.

[0128] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 6%.

[0129] The preparation method of the performance modifier of this embodiment is:

[0130] The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whisker; 8 parts of dry boron carbide whisker and 4 parts of nano-bentonite are added to 8 parts of sodium lignin sulfonate solution by weight, and then 3 parts of dopamine hydrochloride solution and 2 parts of stearic acid are added and mixed and stirred sufficiently. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a performance adjuster.

[0131] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%.

[0132] The underglaze blue glaze of this embodiment is used in the above-mentioned method for preparing an underglaze blue ceramic, comprising a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 25 parts of cobalt oxide, 6 parts of methyl cellulose, 3 parts of manganese oxide and 20 parts of water;

[0133] The glaze matrix comprises the following raw materials in parts by weight:

[0134] 15 parts of modified quartz, 12 parts of dolomite, 10 parts of calcined talc, 7 parts of calcium carbonate, and 5 parts of doped nano-alumina agent.

[0135] The underglaze blue colored ceramic of the present embodiment is prepared by the above-mentioned preparation method of the underglaze blue colored ceramic.

[0136] Embodiment 3: A method for preparing underglaze blue colored ceramics, comprising the following steps:

[0137] Step 1: Preparation of ceramic substrate:

[0138] According to weight, 22.5 parts of ball clay, 12.5 parts of potassium feldspar, 6.5 parts of bentonite, 5.5 parts of wollastonite, 3.5 parts of silicon nitride and 10 parts of water were mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material;

[0139] The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix;

[0140] Step 2: Preparation of underglaze blue glaze:

[0141] First prepare the glaze pigment body, and then prepare the glaze base body;

[0142] The glaze pigment body is prepared by weight from 22.5 parts of cobalt oxide, 4.5 parts of methyl cellulose, 2.5 parts of manganese oxide and 15 parts of water;

[0143] The glaze matrix comprises the following raw materials in parts by weight:

[0144] 12.5 parts of modified quartz, 10 parts of dolomite, 8 parts of calcined talc, 5.5 parts of calcium carbonate, 4 parts of doped nano-alumina agent;

[0145] Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

[0146] The specific steps of the sintering process in this embodiment are:

[0147] First, sinter at 1250°C for 1.5h, then heat to 1315°C at a rate of 3°C / min, keep at that temperature for 4h, and finally air-cool to room temperature.

[0148] The preparation method of the modified quartz body of this embodiment is:

[0149] S01: preheating quartz powder at 62.5°C for 12.5 minutes, then keeping the temperature, and fully mixing 6.5 parts of the kept temperature quartz powder, 4 parts of lanthanum chloride solution and 2 parts of silane coupling agent KH560 by weight to obtain a quartz modifier;

[0150] S02: calcining kaolin at 125°C for 25 min, then heating to 210°C at a rate of 3.5°C / min, keeping the temperature for 10 min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent;

[0151] S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide;

[0152] By weight, 3.5 parts of modified nano boron oxide and 2 parts of nano silica sol were added to 6.5 parts of 5% chitosan solution, and then 2.5 parts of sodium dodecylbenzene sulfonate were added and mixed thoroughly to obtain a treatment solution;

[0153] S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified quartz body.

[0154] The mass fraction of the lanthanum chloride solution of the present embodiment is 3.5%; the speed of the stirring treatment in S03 is 600r / min, and the stirring time is 25min.

[0155] The preparation method of the doped nano-alumina agent of this embodiment is:

[0156] S11: irradiating the nano-alumina in a proton irradiation box for 7.5 minutes at an irradiation power of 375 W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0157] S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid;

[0158] The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent.

[0159] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 4.5%.

[0160] The preparation method of the performance modifier of this embodiment is:

[0161] The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whiskers; 6.5 parts of dried boron carbide whiskers and 3 parts of nano-bentonite are added to 6.5 parts of sodium lignin sulfonate solution by weight, and then 2 parts of dopamine hydrochloride solution and 1.5 parts of stearic acid are added and mixed and stirred sufficiently. After stirring, the mixture is washed with water, filtered and dried to obtain a performance adjuster.

[0162] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 4.5%.

[0163] The underglaze blue glaze of this embodiment is used in the above-mentioned method for preparing an underglaze blue ceramic, comprising a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 22.5 parts of cobalt oxide, 4.5 parts of methyl cellulose, 2.5 parts of manganese oxide and 15 parts of water;

[0164] The glaze matrix comprises the following raw materials in parts by weight:

[0165] 12.5 parts of modified quartz, 10 parts of dolomite, 8 parts of calcined talc, 5.5 parts of calcium carbonate, and 4 parts of doped nano-alumina agent.

[0166] The underglaze blue colored ceramic of the present embodiment is prepared by the above-mentioned preparation method of the underglaze blue colored ceramic.

[0167] Comparative Example 1:

[0168] The difference from Example 3 is that no modified quartz body is added.

[0169] Comparative Example 2:

[0170] The difference from Example 3 is that the quartz modifier in the preparation of the modified quartz body is replaced by quartz powder raw material.

[0171] Comparative Example 3:

[0172] The difference from Example 3 is that no treatment liquid is used in the preparation of the modified quartz body.

[0173] Comparative Example 4:

[0174] The difference from Example 3 is that no modified nano boron oxide is added to the treatment liquid.

[0175] Comparative Example 5:

[0176] The difference from Example 3 is that no nano boron oxide is added to the modified nano boron oxide.

[0177] Comparative Example 6:

[0178] The difference from Example 3 is that no calcined kaolin agent is added to the modified nano boron oxide.

[0179] Comparative Example 7:

[0180] The difference from Example 3 is that nano silica sol and sodium dodecylbenzene sulfonate are not added to the treatment liquid.

[0181] Comparative Example 8:

[0182] The difference from Example 3 is that no doped nano-alumina agent is added.

[0183] Comparative Example 9:

[0184] The difference from Example 3 is that in the preparation of the doped nano-alumina agent, the nano-alumina liquid is made of nano-alumina and deionized water in a weight ratio of 2:5.

[0185] Comparative Example 10:

[0186] The difference from Example 3 is that no sodium silicate solution is added to the nano alumina liquid.

[0187] Comparative Example 11:

[0188] The difference from Example 3 is that no performance modifier is added in the preparation of the doped nano-alumina agent.

[0189] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 11 were subjected to conventional performance tests. The products were placed in 2% hydrochloric acid mist for 12 hours and then in 5% sodium chloride salt mist for 24 hours to test the acid and alkali stability of the products. The products were also immersed in acetone solvent for 48 hours to test the solvent resistance stability of the products. The test results are shown in Table 1.

[0190] Table 1 Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 11:

[0191]

[0192] From comparative examples 1-11 and examples 1-3, as well as tests under acid-base resistance and solvent-resistance conditions, it can be seen that the product of example 3 has excellent lubricity, stain resistance and load resistance, and the three properties can be improved in a coordinated manner, and the product has a significant improvement in performance stability under acid-base and solvent-resistance conditions;

[0193] When neither modified quartz nor doped nano-alumina is added to the product, the performance of the product deteriorates most significantly. When both are used in combination, the product performance effect is most obvious.

[0194] In the preparation of the modified quartz body, the quartz modifier is replaced by quartz powder raw material, the modified quartz body is not treated with a treatment liquid, the treatment liquid is not added with modified nano boron oxide, the modified nano boron oxide is not added with nano boron oxide, the modified nano boron oxide is not added with calcined kaolin agent, and the treatment liquid is not added with nano silica sol and sodium dodecylbenzene sulfonate. The performance of the product has a tendency to deteriorate. The treatment liquid obtained by the specific method of the present invention is combined with the quartz modifier, and the product performance effect is the most significant. The use of other methods instead is not as obvious as the effect of the present invention.

[0195] In the preparation of doped nano-alumina agent, the nano-alumina liquid is made of nano-alumina and deionized water in a weight ratio of 2:5, no sodium silicate solution is added to the nano-alumina liquid, and no performance-adjusting agent is added in the preparation of the doped nano-alumina agent. The performance of the product has a tendency to deteriorate, and the performance-adjusting agent is not added in the preparation of the doped nano-alumina agent. The performance of the product deteriorates more significantly. The doped nano-alumina agent obtained by the specific method of the present invention has the most significant product performance effect.

[0196] The present invention further explores the product performance through the preparation of the performance regulator.

[0197] Experimental Example 1:

[0198] The only difference from Example 3 is that no dry boron carbide whiskers are added in the preparation of the performance modifier.

[0199] Experimental Example 2:

[0200] The only difference from Example 3 is that no nano bentonite is added in the preparation of the performance modifier.

[0201] Experimental Example 3:

[0202] The only difference from Example 3 is that no dopamine hydrochloride solution is added in the preparation of the modulator.

[0203] Experimental Example 4:

[0204] The only difference from Example 3 is that no sodium lignin sulfonate solution and stearic acid are added in the preparation of the conditioning agent.

[0205] Experimental Example 5:

[0206] The only difference from Example 3 is that the mass fraction of the sodium lignin sulfonate solution is 6%; the mass fraction of the dopamine hydrochloride solution is 7%.

[0207] The ceramic products of Experimental Examples 1 to 5 were subjected to conventional performance tests. At the same time, the products were placed in 2% hydrochloric acid mist conditions for 12 hours and then placed in 5% sodium chloride salt mist conditions for 24 hours to test the acid and alkali stability of the products. The products were also immersed in acetone solvent for 48 hours to test the solvent resistance stability of the products. The test results are shown in Table 2.

[0208] Table 2 Performance test results of ceramic products in Experimental Examples 1 to 5:

[0209]

[0210] It can be seen from Experimental Examples 1-5 that dry boron carbide whiskers were not added in the preparation of the performance regulator, and the performance of the product changed. In the preparation of the performance regulator, the performance deterioration was the most obvious, followed by the absence of nano-bentonite. At the same time, no dopamine hydrochloride solution was added in the preparation of the performance regulator, and no sodium lignin sulfonate solution and stearic acid were added in the preparation of the performance regulator. The mass fraction of the sodium lignin sulfonate solution was 6%; the mass fraction of the dopamine hydrochloride solution was 7%. The performance of the products all tended to deteriorate. Only the performance regulator prepared by the specific raw materials of the present invention and the specific mass fraction of the raw materials had the most significant performance effect of the product. The preparation of the performance regulator by other methods was not as significant as that of the present invention. The raw materials and process parameters of the performance regulator of the present invention are unique.

[0211] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0212] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing underglaze blue colored ceramics, characterized in that: The following steps are involved: Step 1: Preparation of ceramic substrate: According to weight, 20-25 parts of ball clay, 10-15 parts of potassium feldspar, 5-8 parts of bentonite, 4-7 parts of wollastonite, 2-5 parts of silicon nitride and 8-12 parts of water are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min to obtain a ball-milled material; The ball abrasive is pressed into a mold at a pressure of 20 MPa for 20 min, and then demolded to obtain a ceramic matrix; Step 2: Preparation of underglaze blue glaze: First prepare the glaze pigment body, and then prepare the glaze base body; The glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water; The glaze matrix comprises the following raw materials in parts by weight: 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent; The preparation method of the modified quartz body is: S01: preheating quartz powder at 60-65°C for 10-15 minutes, then keeping the temperature, and fully mixing 5-8 parts of the kept temperature quartz powder, 3-5 parts of lanthanum chloride solution and 1-3 parts of silane coupling agent KH560 by weight to obtain a quartz modifier; S02: calcining kaolin at 120-130°C for 20-30min, then heating to 200-220°C at a rate of 2-5°C / min, keeping the temperature for 10min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent; S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide; By weight, 2-5 parts of modified nano boron oxide and 1-3 parts of nano silica sol are added to 5-8 parts of 5% chitosan solution, and then 2-3 parts of sodium dodecylbenzene sulfonate are added and mixed thoroughly to obtain a treatment solution; S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, the mixture is washed with water and dried to obtain a modified quartz body; The preparation method of the doped nano-alumina agent is: S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid; The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent. The preparation method of the synergist is as follows: Stirring and mixing boron carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then washing with water, filtering with suction, and drying to obtain dried boron carbide whiskers; adding 5-8 parts of dried boron carbide whiskers and 2-4 parts of nano-bentonite to 5-8 parts of sodium lignin sulfonate solution by weight, then adding 1-3 parts of dopamine hydrochloride solution and 1-2 parts of stearic acid to blend and stir sufficiently, washing with water, filtering with suction, and drying to obtain an efficiency regulator; Step 3: First, apply the glaze pigment to the ceramic substrate with a thickness of 0.1 mm, and then apply the glaze substrate with a glaze amount of 100 g / m 2 , and finally sintered to obtain underglaze blue ceramics.

2. The method for preparing underglaze blue colored ceramics according to claim 1, characterized in that: The specific steps of the sintering process are: First, sinter at 1250°C for 1-2h, then heat to 1310-1320°C at a rate of 2-4°C / min, keep warm for 4h, and finally air-cool to room temperature.

3. The method for preparing underglaze blue colored ceramics according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the speed of the stirring treatment in S03 is 550-750r / min, and the stirring time is 20-30min.

4. The method for preparing underglaze blue colored ceramics according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

5. The method for preparing underglaze blue colored ceramics according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

6. An underglaze blue glaze, used in the method for preparing an underglaze blue ceramic according to any one of claims 1 to 5, characterized in that: The glaze pigment body comprises a glaze pigment body and a glaze matrix, wherein the glaze pigment body is prepared by weight from 20-25 parts of cobalt oxide, 3-6 parts of methyl cellulose, 2-3 parts of manganese oxide and 10-20 parts of water; The glaze matrix comprises the following raw materials in parts by weight: 10-15 parts of modified quartz, 8-12 parts of dolomite, 6-10 parts of calcined talc, 4-7 parts of calcium carbonate, and 3-5 parts of doped nano-alumina agent; The preparation method of the modified quartz body is: S01: preheating quartz powder at 60-65°C for 10-15 minutes, then keeping the temperature, and fully mixing 5-8 parts of the kept temperature quartz powder, 3-5 parts of lanthanum chloride solution and 1-3 parts of silane coupling agent KH560 by weight to obtain a quartz modifier; S02: calcining kaolin at 120-130°C for 20-30min, then heating to 200-220°C at a rate of 2-5°C / min, keeping the temperature for 10min, finally air-cooling to room temperature, and then immersing in a sufficient amount of 4% by mass yttrium nitrate solution and stirring to obtain a calcined kaolin agent; S03: mixing nano boron oxide and calcined kaolin agent in a weight ratio of 2:5, then filtering and drying to obtain modified nano boron oxide; By weight, 2-5 parts of modified nano boron oxide and 1-3 parts of nano silica sol are added to 5-8 parts of 5% chitosan solution, and then 2-3 parts of sodium dodecylbenzene sulfonate are added and mixed thoroughly to obtain a treatment solution; S04: The quartz modifier and the treatment liquid are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, the mixture is washed with water and dried to obtain a modified quartz body; The preparation method of the doped nano-alumina agent is: S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: fully blending the irradiated nano-alumina, the sodium silicate solution and the sodium alginate solution in a weight ratio of 2:5:8 to obtain a nano-alumina liquid; The nano-alumina liquid and the performance-adjusting agent were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a doped nano-alumina agent. The preparation method of the synergist is as follows: The boron carbide whisker is stirred and mixed in a sufficient amount of 5% by mass potassium permanganate solution, and then washed with water, filtered and dried to obtain dry boron carbide whisker; 5-8 parts of dry boron carbide whisker and 2-4 parts of nano-bentonite are added to 5-8 parts of sodium lignin sulfonate solution by weight, and then 1-3 parts of dopamine hydrochloride solution and 1-2 parts of stearic acid are added and mixed and stirred sufficiently, and after stirring, the mixture is washed with water, filtered and dried to obtain a performance adjuster.

7. An underglaze blue-colored ceramic, prepared by the preparation method of an underglaze blue-colored ceramic as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Rare earth daily ceramic glaze and method using rare earth daily ceramic glaze to prepare daily ceramic

    CN108083646A

  • Glaze and tile for high-temperature gold-colored glazed tile, and manufacturing method thereof

    WO2018032127A1